Safety, pharmacokinetics and pharmacodynamics of BI 135585, a selective 11β‐hydroxysteroid dehydrogenase‐1 (HSD1) inhibitor in humans: liver and adipose tissue 11β‐HSD1 inhibition after acute and multiple administrations over 2 weeks. Issue 5 (10th March 2016) - Freude, S.; Heise, T.; Woerle, H.‐J.; Jungnik, A.; Rauch, T.; Hamilton, B.; Schölch, C.; Huang, F.; Graefe‐Mody, U.
Abstract : Aims: To assess the safety and pharmacokinetic and pharmacodynamic characteristics of BI 135585, a selective 11β‐hydroxysteroid dehydrogenase‐1 (11β‐HSD1) inhibitor, after single‐ and repeated‐dose administration. Methods: The single‐dose study included open‐label administration of 200 mg BI 135585 in healthy volunteers, while in the multiple‐dose study, we carried out randomized, double‐blind administration of 5–200 mg BI 135585 or placebo once daily over 14 days in patients with type 2 diabetes (T2DM). Assessments included 11β‐HSD1 inhibition in the liver (urinary tetrahydrocortisol (THF)/tetrahydrocotisone (THE) ratio) and in subcutaneous adipose tissue (AT) ex vivo and determination of hypothalamus‐pituitary‐adrenal (HPA) axis hormone levels. Results: No major safety issues occurred with BI 135585 administration. The HPA axis was mildly activated with slightly increased, but still normal adrenocorticotropic hormone levels, increased total urinary corticoid excretion but unchanged plasma cortisol levels. After multiple doses of 5–200 mg BI 135585, exposure (area under the curve) increased dose‐proportionally and half‐life was 55–65 h. The urinary THF/THE ratio decreased, indicating liver 11β‐HSD1 inhibition. Median 11β‐HSD1 enzyme inhibition in the AT reached 90% after a single dose of BI 135585, but was low (31% or lower) after 14 days of continuous treatment. Conclusions: BI 135585 was safe and well tolerated over 14 days and can be dosed once daily. Future studies are required to clarify the therapeutic potential of BI 135585 in view of its effects on 11β‐HSD1 inhibition in AT after single and multiple doses. Enzyme inhibition in the AT was not adequately predicted by the urinary THF/THE ratio.